A new implementation of digital X-ray radiogrammetry and reference curves of four indices of cortical bone for healthy European adults. Issue 1 (December 2016) - Thodberg, Hans; Böttcher, Joachim; Lomholt, Jens; Kreiborg, Sven; Wolf, Gunter; Pfeil, Alexander
Abstract Summary Digital X-ray radiogrammetry performs measurements on a hand radiograph in digital form. We present an improved implementation of the method and provide reference curves for four indices for the amount of bone. We collected 1662 hand radiographs of healthy subjects of age 9–100 years. Purpose The digital X-ray radiogrammetry (DXR) method has been shown to be efficient for diagnosis of osteoporosis and for assessment of progression of rheumatoid arthritis. The aim of this work is to present a new DXR implementation and reference curves of four indices of cortical bone and to compare their relative SDs in healthy subjects at fixed age and gender. Materials and methods A total of 1662 hand radiographs of healthy subjects of age 9–100 years were collected in Jena in 2001–2005. We also used a longitudinal study of 116 Danish children born in 1952 with on average 11 images taken over the age range 7 to 40 years. The new DXR method reconstructs the whole metacarpal contour so that the metacarpal lengths can be measured and used in two of the indices. The new DXR method automatically validates 97 % of the images and is implemented as a local server for PACS users. Results The Danish bone health index (BHI) data are consistent with the Jena data and also with the published BHI reference for healthy children. BHI is found to have smaller relative SD than the other three indices in the Jena cohort over the age range 20–80 years. Conclusion The new DXR method is an extension of the existing BoneXpert method for children, which allows patients to be followed from childhood into adulthood with the same method. By making all four indices of cortical bone available within the same medical device, it becomes possible to decide which index has the best relation to fracture risk in future studies.